Impact of Intravenous Nitrate Treatment on Antiplatelet Effects of Clopidogrel in Acute Coronary Syndrome Patients: A Pilot Study - Mehmet Melek MD; Hasan Ari MD; Alper Karakuş MD; Selma Ari MD; Ahmet Tütüncü MD; Tahsin Bozat MD (Journal of Cardiovascular Pharmacology and Therapeutics)
Background Clopidogrel is a pro-drug that requires metabolic activation by hepatic cytochrome P450 (CYP) enzymes in two steps. Previous studies have shown that the administration of continuous nitrate significantly affects the activity of hepatic CYP. In this pilot study, we assess the impact of intravenous nitrate treatment on the antiplatelet effects of clopidogrel in patients with non-ST-elevation myocardial infarction (NSTEMI). Method We included 20 NSTEMI patients: 15 in the nitrate group and five in the control group. All patients received a 300 mg acetylsalicylic acid and a 600 mg clopidogrel loading dose. The nitrate group was administered an intravenous glyceryl trinitrate infusion at 10 µg/min for 48 h. After the drugs were initiated, blood samples were collected from patients at intervals of 30th minutes, 60th minutes, 120th minutes, fourth hour, sixth hour, and 48th hour to assess platelet function. The antiplatelet effect of clopidogrel was evaluated using the platelet reactivity unit (PRU) from the Verify-Now P2Y12 assay. Result The PRU values at baseline and the 30th, 60th, 120th minutes, and 48th hour were similar between the two groups ( P  > .05). However, PRU values at the fourth and sixth hours were significantly higher in the nitrate group than in the control group (274.1 ± 53.9 vs 162.4 ± 39.9; P  = .002 and 272.0 ± 67.0 vs 185.6 ± 18.1; P  = .03, respectively). Conclusion Intravenous nitrate therapy in patients with NSTEMI delayed the onset of the antiplatelet effect of orally loaded clopidogrel by at least 4 h. This point should be kept in mind in patients using clopidogrel and nitrate therapy together. (NCT06878638)